The Houstouns of Georgia - Houston, Rab (Georgia Open History Library, 1950)
The Houstouns of Georgia shares the history of one of the oldest families in Georgia, showcasing its influential members and reflecting on the effect of one family throughout the state's history. Established by Sir Patrick Houstoun, who accompanied James Oglethorpe and helped him lay the foundations of the colony, the Houstoun family has called Georgia home since its inception. Over two hundred years after its founding, the author of The Houstouns of Georgia traces her own lineage back to the Houstoun family in her heavily researched account of the family's presence in Georgia from its founding onward. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.